2019
DOI: 10.1111/bjhp.12379
|View full text |Cite
|
Sign up to set email alerts
|

‘We're all in the same boat’: A qualitative study on how groups work in a diabetes prevention and management programme

Abstract: What is already known on this subject?Many health interventions, including programmes to help prevent or manage diabetes and facilitate weight loss, are delivered in groups. Such group-based behaviour-change interventions are often effective in facilitating psychological and behaviour change. There is considerable research and theory on individual change processes and techniques, but less is known about which change processes and techniques facilitate behaviour change in group settings. What does this study ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…It was also felt that group sizes needed to be manageable in order for facilitators to provide personalized advice. Similarly, it was reported that shared experiences facilitated problem solving and bolstered self-efficacy in the Norfolk Diabetes Prevention Study [ 29 ]. Furthermore, our findings regarding participants’ valuing having their bodyweight monitored are in line with findings from the same study, where weigh-ins within the group setting were found to give participants a sense of accountability.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…It was also felt that group sizes needed to be manageable in order for facilitators to provide personalized advice. Similarly, it was reported that shared experiences facilitated problem solving and bolstered self-efficacy in the Norfolk Diabetes Prevention Study [ 29 ]. Furthermore, our findings regarding participants’ valuing having their bodyweight monitored are in line with findings from the same study, where weigh-ins within the group setting were found to give participants a sense of accountability.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Trust is fundamentally important in the management of DM from both the physical and psychological points of view (42). We found that only 27.6% of patients with DM with access to the internet fully trusted online information.…”
Section: Discussionmentioning
confidence: 80%
“…This could suggest prior social ties might facilitate successful outcomes. However, feelings of social cohesion can also develop through the process of participation in group-oriented programs where individuals may not be previously acquainted ( Canuto et al, 2013 , Borek et al, 2019 ), particularly where there is homogeneity in a group ( Farrance et al, 2016 ). Moreover, the impact of social cohesion may be intertwined with group leader characteristics ( Izumi et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%